Aplikasi Pembelajaran Manasik Haji dan Umroh berbasis Multimedia dengan Metode User Centered Design (UCD) - Utomo, Rahmad Budi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
Multimedia development as one field of application in audio-visual technology seemed never to be separated from human needs of customers who desire a new innovation in every design and user friendly of an application. Build a complex software system design models require systematic for analysis and design. By using the language of the Unified Modeling Language (UML) a job can be easily designed, because UML is a visual modeling notation and semantics and object-oriented analysis and design. The requirement applications that can help candidate of Hajj and Umroh to learn the background of the application design learning the rituals of Hajj and Umrah this multimedia based. The design of the rituals of Hajj and Umroh application-based multimedia is created using Adobe Flash Professional software and Adobe Audition CS 6 CS 6 as the supporting software. This application can be integrated with android software which uses methods of UCD (User Centered Design) from the research that has been done.